Analysis of the Birth Insurance Program (Jampersal) utilization in Bangli District, Bali, Indonesia - Ni Made Ayu Kemala Dewi; Yuli Kurniati; Pande Putu Januraga (Universitas Udayana, 2020)
Background and purpose: The Birth Insurance Program or called Jaminan Persalinan (Jampersal) aims to reduce maternal and newborn deaths. Bangli is one of the districts in Indonesia with low utilisation of Jampersal program. The study aims to explore factors associated with the low utilization and uptake of Jampersal Program in Bangli District. Methods: This was a qualitative study conducted between April- May 2019. The study involved 24 informants who were selected purposively. The informants were 18 pregnant women, two community leaders, three health workers and one Bangli Health Office’s staff. Data were collected through in-depth interviews which explore factors associated to utilisation of Jampersal using PRECEDE-PROCEED Framework. Data were analyzed by thematic analysis. Results: We found that informants who used Jampersal had sufficient knowledge about Jampersal, were exposed to the program informed by health workers and community leaders, and were supported by their families. Whereas, those who yet to utilize Jampersal had a poor understanding on Jampersal service mechanisms, lack of spousal support in preparing Jampersal requirements and private midwives had not signed the Jampersal MoU. Conclusion: Low utilisation of Jampersal Program in Bangli District partially influenced by low understanding of the program and in-optimal involvement of midwifery networks. The local health office should further expand cooperation with the private midwife network for optimum utilization of Jampersal, elucidation of the Jampersal technical guidelines to health workers, as well as technical support for participants in completing required documents.